Transcription Coactivator ANGUSTIFOLIA3 (AN3) Regulates Leafy Head Formation in Chinese Cabbage - Yu, Jing; Gao, Liwei; Liu, Wusheng; Song, Lixiao; Xiao, Dong; Liu, Tongkun; Hou, Xilin; Zhang, Changwei (Frontiers in Plant Science, 2019)
Leafy head formation in Chinese cabbage (B. rapa ssp. pekinensis cv. Bre) results from leaf curvature, which is under the tight control of genes involved in the adaxial-abaxial patterning during leaf development. The transcriptional coactivator ANGUSTIFOLIA3 (AN3) binds to the SWI/SNF chromatin remodeling complexes formed around ATPases such as BRAHMA (BRM) in order to regulate transcription in various aspects of leaf development such as cell proliferation, leaf primordia expansion, and leaf adaxial/abaxial patterning in Arabidopsis. However, its regulatory function in Chinese cabbage remains poorly understood. Here, we analyzed the expression patterns of the Chinese cabbage AN3 gene (BrAN3) before and after leafy head formation, and produced BrAN3 gene silencing plants by using the turnip yellow mosaic virus (TYMV)-derived vector in order to explore its potential function in leafy head formation in Chinese cabbage. We found that BrAN3 had distinct expression patterns in the leaves of Chinese cabbage at the rosette and heading stages. We also found silencing of BrAN3 stimulated leafy head formation at the early stage. Transcriptome analysis indicated that silencing of BrAN3 modulated the hormone signaling pathways of auxin, ethylene, GA, JA, ABA, BR, CK and SA in Chinese cabbage. Our study offers unique insights into the function of BrAN3 in leafy head formation in Chinese cabbage.